Psychosocial stress on neuroinflammation and cognitive dysfunctions in Alzheimer's disease: the emerging role for microglia?. (June 2017) - Piirainen, Sami; Youssef, Andrew; Song, Cai; Kalueff, Allan V.; Landreth, Gary E.; Malm, Tarja; Tian, Li
Highlights: Psychosocial stress primes microglia that contributes to synaptic dysfunctions. Psychosocial stress exacerbates synaptic dysfunction, cognitive impairment in AD. The detrimental effect may be via stress-induced abnormal microglial functions. Abstract: Chronic psychosocial stress is increasingly recognized as a risk factor for late-onset Alzheimer's disease (LOAD) and associated cognitive deficits. Chronic stress also primes microglia and induces inflammatory responses in the adult brain, thereby compromising synapse-supportive roles of microglia and deteriorating cognitive functions during aging. Substantial evidence demonstrates that failure of microglia to clear abnormally accumulating amyloid-beta (Aβ) peptide contributes to neuroinflammation and neurodegeneration in AD. Moreover, genome-wide association studies have linked variants in several immune genes, such as TREM2 and CD33, the expression of which in the brain is restricted to microglia, with cognitive dysfunctions in LOAD. Thus, inflammation-promoting chronic stress may create a vicious cycle of aggravated microglial dysfunction accompanied by increased Aβ accumulation, collectively exacerbating neurodegeneration. Surprisingly, however, little is known about whether and how chronic stress contributes to microglia-mediated neuroinflammation that may underlie cognitive impairments in AD. This review aims to summarize the currently available clinical and preclinical data and outline potential molecular mechanisms linking stress, microglia and neurodegeneration, to foster future research in this field.